2008
DOI: 10.1160/th07-10-0601
|View full text |Cite
|
Sign up to set email alerts
|

Detection of P2Y14 protein in platelets and investigation of the role of P2Y14 in platelet function in comparison with the EP3 receptor

Abstract: SummarymRNA encoding the recently discovered P2Y14 receptor has been reported in platelets, but the presence of P2Y14 receptor protein and its functionality have not been studied. If P2Y14 is expressed along with P2Y1 and P2Y12 receptors it may have a role in haemostasis. It was the objective of this study to investigate the presence of the P2Y14 receptor in platelets and its role in platelet function. The effects of the agonist UDP-glucose were compared with those of sulprostone, a selective EP3 receptor agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Mice were administered a second P2Y12 antagonist (Ticagrelor). However this did not lead to a suppression of pulmonary neutrophil recruitment induced by LPS at 3mg/kg or 10mg/kg Given that P2Y1, P2Y12, P2Y14, and P2X1 receptors are all expressed on platelets, and platelet activation is necessary for pulmonary leukocyte recruitment in this model of inflammation [12,22,27,38], we further examined the effects of these receptors on platelet dynamics (in vivo) and platelet-neutrophil interactions (in vitro).…”
Section: Activation Of P2y1 and P2y14 But Not P2y12 Or P2x1 Receptorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice were administered a second P2Y12 antagonist (Ticagrelor). However this did not lead to a suppression of pulmonary neutrophil recruitment induced by LPS at 3mg/kg or 10mg/kg Given that P2Y1, P2Y12, P2Y14, and P2X1 receptors are all expressed on platelets, and platelet activation is necessary for pulmonary leukocyte recruitment in this model of inflammation [12,22,27,38], we further examined the effects of these receptors on platelet dynamics (in vivo) and platelet-neutrophil interactions (in vitro).…”
Section: Activation Of P2y1 and P2y14 But Not P2y12 Or P2x1 Receptorsmentioning
confidence: 99%
“…Using a murine model of allergic airway inflammation we have previously demonstrated that pulmonary leukocyte recruitment was mediated via RhoA signalling downstream of the platelet P2Y1 receptor, whilst the P2Y12 and P2X1 receptors showed no involvement in this process [26]. More recently, platelets have been shown to express the P2Y14 receptor on their surface [27]. However, the P2Y14 receptor appears to be redundant in platelet aggregation, whilst demonstrating an ability to mediate cell migration in other cell types [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets express four P2 receptors (ATP‐gated P2X 1 ion channel and the G protein‐coupled receptors [GPCRs] P2Y 1 and P2Y 12 —both activated by ADP, P2Y 14 —activated by UDP‐glucose) and two P1 receptors:‐ the adenosine activated GPCRs A 2A and A 2B receptors (Gachet, 2006 ; Jacobson et al, 2011 ; Wolska & Rozalski, 2019 ). The relevance of P2Y 14 activation of platelets has not been extensively described, but P2Y 14 appears to lack an involvement in platelet aggregation, while preliminary data suggest P2Y 14 might be involved in platelet‐associated neutrophil migration (Amison et al, 2017 ; Dovlatova et al, 2008 ). Elsewhere, a direct role for P2Y 14 on leukocyte activation has been reported (Sesma et al, 2012 , 2016 ).…”
Section: The Functions Of Platelets In Inflammation Compared With Hae...mentioning
confidence: 99%